2021
DOI: 10.1007/s10863-021-09905-4
|View full text |Cite
|
Sign up to set email alerts
|

TSPO protein binding partners in bacteria, animals, and plants

Abstract: The ancient membrane protein TSPO is phylogenetically widespread from archaea and bacteria to insects, vertebrates, plants, and fungi. TSPO’s primary amino acid sequence is only modestly conserved between diverse species, although its five transmembrane helical structure appears mainly conserved. Its cellular location and orientation in membranes have been reported to vary between species and tissues, with implications for potential diverse binding partners and function. Most TSPO functions relate to stress-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 241 publications
(554 reference statements)
0
32
0
Order By: Relevance
“…TSPO proteins are highly evolutionarily conserved, being found in eukaryotes, bacteria and archaea [154,155]. Like PGRMC1, mammalian TSPO's functions remain elusive.…”
Section: Potential Early Eukaryotic Mapr Functions Deduced From Moder...mentioning
confidence: 99%
“…TSPO proteins are highly evolutionarily conserved, being found in eukaryotes, bacteria and archaea [154,155]. Like PGRMC1, mammalian TSPO's functions remain elusive.…”
Section: Potential Early Eukaryotic Mapr Functions Deduced From Moder...mentioning
confidence: 99%
“…TSPO is an integral protein in health whose activation can regulate cell death and promote protective and restorative responses. [31][32][33] Despite numerous studies of TSPO's role in mitochondrial function, 34 no studies have revealed why its decline in LCs leads to mitochondrial dysfunction or how this relates to reduced steroid formation. To study the potential role of TSPO in the regulation of mitochondrial function, we utilized a TSPO knockout (KO) nG1 MA-10 sub-cell line, 13 isolated LCs from rats containing a Tspo deletion, 35 and LCs isolated from aging rats with reduced TSPO levels.…”
Section: Introductionmentioning
confidence: 99%
“…Comparison of membrane protein reconstituted either in synthetic lipids or in bacterial cellular envelopes shows a decrease of resolution for the latter, which can be due to the presence of partners that very likely stabilizes different coexisting conformations important for the biological function [68]. TSPO functional state has been described to be linked to interaction with different partners [69]. Thus, the optimization of protein-lipids interactions and/or the presence of functional partner(s) might help in finding stabilizing conditions for mTSPO and in solving the structural heterogeneity.…”
Section: Discussionmentioning
confidence: 99%